Spatially Explicit Wastewater Generation and Tracking (SEWAGE-TRACK) in the Middle East and North Africa Region - Velpuri, Naga Manohar; Mateo-Sagasta, Javier; Orabi, Mohamed O.M. (Elsevier, 2023)
This study developed the SEWAGE-TRACK model for disaggregating lumped national wastewater generation estimates using population datasets and quantifying rural and urban wastewater generation and fate. The model allocates wastewater into riparian, coastal, and inland components and summarizes the fate of wastewater into productive (direct and indirect reuse) and unproductive components for 19 countries in the Middle East and North Africa (MENA) region. As per the national estimates, 18.4 km3 of municipal wastewater generated in 2015, was disaggregated over the MENA region. Results from this study revealed urban and rural areas to contribute to 79 % and 21 % of municipal wastewater generation respectively. Within the rural context, inland areas generated 61 % of the total wastewater. The riparian and coastal regions produced 27 % and 12 %, respectively. Within the urban settings, riparian areas produced 48 %, while inland and coastal regions generated 34 % and 18 % of the total wastewater, respectively. Results indicate that 46 % of the wastewater is productively used (direct reuse and indirect use), while 54 % is lost unproductively. Of the total wastewater generated, the most direct use was observed in the coastal areas (7 %), the most indirect reuse in the riparian regions (31 %), and the most unproductive losses in inland areas (27 %). The potential of unproductive wastewater as a non-conventional freshwater source was also analyzed. Our results indicate that wastewater is an excellent alternative water source and has high potential to reduce pressure on non-renewable sources for some countries in the MENA region. The motivation of this study is to disaggregate wastewater generation and track wastewater fate using a simple but robust approach that is portable, scalable and repeatable. Similar analysis can be done for other regions to produce information on disaggregated wastewater and its fate. Such information is highly critical for efficient wastewater resource management.